Prevalence and antibiotic resistance pattern of Metallo-β-lactamase-producing Pseudomonas aeruginosa isolates from clinical specimens in a tertiary care hospital - Vinita Choudhary; Nita Pal; Saroj Hooja (Wolters Kluwer Medknow Publications, 2019)
Background: Pseudomonas aeruginosa is emerging as a nosocomial pathogen by producing metallo-β-lactamases (MBLs) and acquiring resistance to many antimicrobial agents. The infections caused by metallo-beta-lactamases producing P. aeruginosa (MBL-PA) are associated with higher rates of mortality, morbidity, and overall healthcare costs. Aim: The aim of the study was to find the incidence of MBL in P. aeruginosa isolates and their antimicrobial resistance pattern. Material and Methods: A total of 180 non-duplicate P. aeruginosa isolates from various clinical specimens between April 2016 and March 2017 were subjected to susceptibility testing by disc diffusion test as per the Clinical and Laboratory Standards Institute guidelines 2015. Imipenem and meropenem resistant isolates were selected for the detection of MBL production by disc potentiation test and modified Hodge test. Results: Out of 180 isolates of P. aeruginosa, MBL was detected in 36 (20.00%) isolates. Resistance was significantly higher in the MBL-PA with 94.44% resistance to aztreonam followed by cefoxitin (91.66%), piperacilline/tazobactam and cefepime (80.55%). The prevalence of multidrug-resistant and possible extensively drug-resistant isolates was significantly higher among the MBL group as compared to that in the non-MBL group [50.00% vs. 11.11% and 5.55% vs. 0.69% (P = <0.05)]. None of the isolates were pan drug resistant. Conclusions: Increasing prevalence of MBL-PA producing isolates in hospital settings makes it important to perform routine detection of MBL strains for the purpose of infection control and for minimizing the adverse outcome of infection.